Prepreg, and metal-clad laminate and wiring board using the same

By using a prepreg containing a thermosetting resin composition of phenolic resin, epoxy resin, maleimide compound and benzoxazine compound and glass cloth, the warping problem of the wiring board is solved, and low dielectric properties and low coefficient of thermal expansion are achieved, meeting the requirements of high frequency signal transmission.

CN123036327APending Publication Date: 2026-11-03PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580024482.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-27
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

In the prior art, the wiring boards of electronic devices are prone to warping when semiconductor chips are installed, and it is difficult to meet the requirements of low dielectric properties and low coefficient of thermal expansion for high-frequency signal transmission.

Method used

A thermosetting resin composition comprising phenolic resin, epoxy resin, maleimide compound and benzoxazine compound, and a glass cloth prepreg are used to form a metal foil laminate and a wiring board. By optimizing the material composition and structural design, low dielectric properties and low coefficient of thermal expansion are achieved.

Benefits of technology

It effectively suppresses board warping, improves signal transmission speed, meets the low loss requirements of high-frequency signals, and reduces the coefficient of thermal expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036327A_ABST
    Figure CN123036327A_ABST
Patent Text Reader

Abstract

One aspect of the present application relates to a prepreg comprising: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and a glass cloth, wherein the thermosetting resin composition contains at least one of a phenol resin (A), an epoxy resin (B), and a maleimide compound (C), and the glass cloth contains, relative to the total amount of components of the glass cloth: 45 to 55 mass% of SiO2; 20 to 30 mass% of Al2O3; 3.0 mass% or less of MgO; and 10 to 15 mass% of P2O5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to prepregs, and foil-coated laminates and wiring boards using the prepregs. Background Technology

[0002] For various electronic devices, with the increasing volume of information processing, mounting technologies such as high integration of semiconductor devices, high-density wiring, and multilayering are becoming increasingly advanced. Furthermore, wiring boards used in various electronic devices require high-frequency applications, such as millimeter-wave radar substrates for automotive applications. For wiring boards used in various electronic devices, reducing signal transmission losses is required to improve signal transmission speed; this requirement is particularly important for high-frequency wiring boards. To meet this requirement, the substrate material used to construct the wiring boards used in various electronic devices requires low dielectric properties.

[0003] As a substrate material, glass fiber reinforced resin molded articles (Patent Document 1) have been reported, for example, including glass fibers and thermoplastic or thermosetting resins, wherein the glass fibers have the following composition: relative to the total amount of glass fibers, they include: 60.00 to 70.00% by mass of SiO2, 20.00 to 30.00% by mass of Al2O3, 5.00 to 15.0% by mass of MgO, 0.15 to 1.50% by mass of Fe2O3, and a total of 0.02 to 0.20% by mass of Li2O, Na2O, and K2O. In addition, glass fiber reinforced resin molded articles (Patent Document 2) are also reported, which include glass fibers and thermoplastic or thermosetting resins, wherein the glass fibers have the following composition relative to the total amount of glass fibers: 52.0 to 57.0% by mass of SiO2, 13.0 to 17.0% by mass of Al2O3, 15.0 to 21.5% by mass of B2O3, 2.0 to 6.0% by mass of MgO, 2.0 to 6.0% by mass of CaO, 1.0 to 4.0% by mass of TiO2, less than 1.5% by mass of F2, and the total amount of Li2O, Na2O and K2O is less than 0.6% by mass.

[0004] In addition, a laminate made by multi-layering the following layers (Patent Document 3) has also been reported, namely: a layer containing a cured composition of E glass (glass fiber containing 80% or less of SiO2 and Al2O3) and a thermosetting resin composition; and a layer containing a cured composition of S glass (glass fiber containing 80% or more of SiO2 and Al2O3) and a thermosetting resin composition.

[0005] While the glass fibers described in Patent Documents 1-3 possess low dielectric properties and high tensile modulus, the increasing performance of electronic devices and the significant improvement in information communication speeds in recent years have led to demands for semiconductor packaging substrates that can accommodate the increasing size and micro-processing of packages, requiring substrate materials with even better low dielectric properties. Furthermore, particularly with the trend towards thinner and larger wiring boards, the following problem arises: warping of semiconductor packages with semiconductor chips mounted on the wiring board can easily lead to poor mounting. To suppress warping of semiconductor packages with semiconductor chips mounted on the wiring board, the substrate material constituting the insulating layer of the wiring board is also required to have a low coefficient of thermal expansion in its cured form.

[0006] The present invention was made in view of the above circumstances, and its object is to provide a prepreg with excellent low dielectric properties and a low coefficient of thermal expansion, and a metal foil laminate and wiring board using the prepreg.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: International Patent Publication No. 2022 / 075273

[0010] Patent Document 2: International Patent Publication No. 2017 / 171101

[0011] Patent Document 3: International Patent Publication No. 2020 / 130007 Summary of the Invention

[0012] The inventors conducted dedicated research to solve the above-mentioned problems and found that the above-mentioned problems could be solved by the following configuration. Based on this insight, they conducted further research and completed the present invention.

[0013] One technical solution of the present invention relates to a prepreg comprising: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains at least one of phenolic resin (A), epoxy resin (B), and maleimide compound (C), and the glass cloth contains, relative to the total amount of the glass cloth, 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0014] One technical solution of the present invention relates to a metal foil laminate comprising: an insulating layer containing the prepreg and a cured material; and a metal layer.

[0015] One technical solution of the present invention relates to a wiring board comprising: an insulating layer comprising a cured prepreg; and wiring. Attached Figure Description

[0016] Figure 1 This is a schematic cross-sectional view showing the structure of a prepreg according to an embodiment of the present invention.

[0017] Figure 2 This is a schematic cross-sectional view illustrating the structure of a metal foil laminate according to an embodiment of the present invention.

[0018] Figure 3 This is a schematic cross-sectional view showing the structure of a wiring board according to an embodiment of the present invention. Detailed Implementation

[0019] The following describes the embodiments of the present invention, but the present invention is not limited to these embodiments.

[0020] <Prepreg>

[0021] The prepreg of this embodiment includes: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains at least one of phenolic resin (A), epoxy resin (B), and maleimide compound (C), and the glass cloth contains, relative to the total amount of the glass cloth, 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0022] The prepreg of this embodiment with this configuration has excellent low dielectric properties and low coefficient of thermal expansion. Therefore, the metal foil laminate and wiring board obtained using the prepreg of this embodiment have excellent low dielectric properties (especially low relative permittivity) and can also suppress warping.

[0023] The following is a detailed description of each component of the prepreg involved in this embodiment.

[0024] [Thermosetting resin composition]

[0025] The thermosetting resin composition (hereinafter also referred to as the "resin composition") involved in this embodiment contains at least one of phenolic resin (A), epoxy resin (B) and maleimide compound (C).

[0026] (Phenolic resin (A))

[0027] As phenolic resin (A), compounds having functional groups with hydroxyl groups bonded to aromatic rings within the molecule can be used, such as bisphenol A type phenolic resin, bisphenol E type phenolic resin, bisphenol F type phenolic resin, bisphenol S type phenolic resin, phenolic varnish resin, bisphenol A phenolic varnish type phenolic resin, glycidyl ester type phenolic resin, aralkyl phenolic varnish type phenolic resin, biphenyl aralkyl type phenolic resin, cresol phenolic varnish type phenolic resin, polyfunctional phenolic resin, naphthol resin, naphthol phenolic varnish resin, polyfunctional naphthol resin, anthracene type phenolic resin, naphthalene skeleton modified phenolic varnish type phenolic resin, phenol aralkyl type phenolic resin, naphthol aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, biphenyl type phenolic resin, alicyclic phenolic resin, polyol type phenolic resin, phosphorus-containing phenolic resin, phenolic resin containing polymerizable unsaturated hydrocarbon groups, and organosilicon resins containing hydroxyl groups, etc. Among these, phenolic varnish resin and bisphenol A type phenolic resin are preferred.

[0028] As for phenolic resin (A), one type of phenolic resin as described above may be used alone, or two or more may be used in combination, depending on the circumstances.

[0029] (Epoxy Resin (B))

[0030] As for epoxy resin (B), there is no particular limitation as long as it is an epoxy resin that can be used in the manufacture of various organic substrates in laminates or circuit boards. Specifically, examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, aralkyl epoxy resin, phenolic varnish type epoxy resin, alkylphenolic varnish type epoxy resin, biphenyl type epoxy resin, biphenylene type epoxy resin, bisphenol type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, epoxidation products of condensates of phenols and aromatic aldehydes having phenolic hydroxyl groups, triglycidyl isocyanate, and alicyclic epoxy resins. Among these, biphenylene type epoxy resin and naphthalene type epoxy resin are preferred.

[0031] As for epoxy resin (B), one type of epoxy resin as described above can be used alone, or two or more types can be used in combination, depending on the circumstances.

[0032] (maleimide compound (C))

[0033] The maleimide compound (C) can be used without particular limitation as long as it is a compound having a maleimide group within its molecule. Specifically, examples of maleimide compounds (C) include: monofunctional maleimide compounds having one maleimide group within their molecule; polyfunctional maleimide compounds having two or more maleimide groups within their molecule; and modified maleimide compounds. Examples of modified maleimide compounds include: modified maleimide compounds in which a portion of the molecule is modified by an amine compound; modified maleimide compounds in which a portion of the molecule is modified by an organosilicon compound; and modified maleimide compounds in which a portion of the molecule is modified by both an amine compound and an organosilicon compound.

[0034] More specifically, examples include: maleimide compounds having two or more N-substituted maleimide groups within one molecule, maleimide compounds having an indane structure, maleimide compounds having at least one selected from an alkyl group having six or more carbon atoms and an alkylene group having six or more carbon atoms, and maleimide compounds having a benzene ring within one molecule.

[0035] Among these, maleimide compounds having two or more N-substituted maleimide groups within one molecule and maleimide compounds having a benzene ring within the molecule are preferred.

[0036] The maleimide compound (C) used in this embodiment can be a commercially available product, such as BMI-4000, BMI-2300, BMI-TMH, BMI-4000, BMI-5100 manufactured by Daiwa Chemical Industries, Ltd.; MIR-3000-70MT and MIR-5000 manufactured by Nippon Kayaku Co., Ltd.; and BMI-689, BMI-1500, BMI-3000J, and BMI-5000 manufactured by Designer Molecules Inc.

[0037] Maleimide compound (C) can be used alone or in combination with two or more maleimide compounds as described above.

[0038] (Benzoxazine compound (D))

[0039] The thermosetting resin composition preferably contains a benzoxazine compound (D). By including a benzoxazine compound (D) in the resin composition, the cured resin composition exhibits excellent adhesion (bonding strength) to a metal layer (e.g., copper foil) and the coefficient of thermal expansion is reliably reduced. The benzoxazine compound (D) is not particularly limited to any compound having at least one benzoxazine ring. Examples include benzoxazine compounds having an alkenyl group within the molecule.

[0040] Benzoxazine compounds having an alkenyl group within the molecule contain not only an alkenyl group but also a benzoxazine group. The alkenyl group is not particularly limited, and examples include alkenyl groups having 2 to 6 carbon atoms. Specifically, examples of the alkenyl group include vinyl, allyl, propenyl, and butenyl groups, with allyl and propenyl being preferred, and allyl being more preferred. That is, benzoxazine compound (D) preferably includes benzoxazine compound (D-1) having an allyl group within the molecule.

[0041] Examples of the benzoxazine group include, for example, the benzoxazine group shown in formula (1) and the benzoxazine group shown in formula (2). As a benzoxazine compound (D), examples include not only benzoxazine compounds having the benzoxazine group shown in formula (1) and benzoxazine compounds having the benzoxazine group shown in formula (2) in the molecule, but also benzoxazine compounds having both the benzoxazine group shown in formula (1) and the benzoxazine group shown in formula (2) in the molecule.

[0042]

[0043] In formula (1), R1 represents allyl, and a represents 1 to 4. a is the average value of the degree of substitution of R1, which is 1 to 4, preferably 1.

[0044]

[0045] In formula (2), R2 represents allyl.

[0046] As an allyl benzoxazine compound (D-1), more specifically, benzoxazine compounds represented by the following formula (3) can be listed.

[0047]

[0048] In the formula (3), R3 and R4 represent allyl, Y represents alkylene, and b and c each independently represent 1 to 4.

[0049] The alkylene group is not particularly limited, and examples include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, eicosyl, and hexadecyl. Among them, methyl is preferred.

[0050] In equation (3), b is the average degree of substitution of R3, which is 1 to 4, preferably 1. Furthermore, in equation (3), c is the average degree of substitution of R4, which is 1 to 4, preferably 1.

[0051] As a benzoxazine compound (D), commercially available products can also be used, such as "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd.

[0052] As a benzoxazine compound (D), the benzoxazine compounds exemplified above can be used alone, or two or more can be used in combination.

[0053] (Elastomer (E))

[0054] The thermosetting resin composition preferably contains an elastomer (E) comprising at least one of a high molecular weight substance (E-1) with a weight average molecular weight of 10,000 or more and 900,000 or less, and a core-shell rubber (E-2).

[0055] It is believed that by including a high molecular weight substance (E-1) with a weight-average molecular weight (Mw) of 10,000 or more and 900,000 or less in the thermosetting resin composition, a lower coefficient of thermal expansion can be obtained in the cured product. More preferably, the high molecular weight substance (E-1) has a weight-average molecular weight (Mw) of 10,000 or more and 600,000 or less. In this specification, the weight-average molecular weight is simply a molecular weight obtained by conventional molecular weight determination methods; specifically, values ​​obtained using gel permeation chromatography (GPC) can be cited.

[0056] The high molecular weight material (E-1) preferably comprises at least one of an acrylic resin and a styrene copolymer with a weight average molecular weight of 10,000 or more and 900,000 or less. By including at least one of an acrylic resin and a styrene copolymer in the high molecular weight material (E-1), a lower coefficient of thermal expansion can be obtained in the cured product.

[0057] As a specific acrylic resin in this embodiment, it is preferred to have the structure shown in the following formulas (4), (5) and (6).

[0058]

[0059]

[0060]

[0061] In the above equations (4) to (6), x, y, and z represent mole fractions and satisfy x + y + z ≤ 1, 0 < x ≤ 0.2, 0.6 ≤ y ≤ 0.95, and 0.05 ≤ z ≤ 0.2.

[0062] In the above formula (5), R5 is a hydrogen atom or a methyl group, and R6 includes at least one of a glycidyl group and an epoxidized alkyl group among a hydrogen atom, an alkyl group, a glycidyl group and an epoxidized alkyl group.

[0063] In the above formula (6), R7 is a hydrogen atom or a methyl group, and R8 is Ph (phenyl), -COOCH2Ph ​​or -COO(CH2)2Ph.

[0064] Preferably, the main chain of the acrylic resin has at least one structure shown in formula (4), at least one structure shown in formula (5), and at least one structure shown in formula (6).

[0065] When the main chain of the acrylic resin has the structures shown in formulas (4), (5), and (6), the configuration order of the structures shown in formulas (4), (5), and (6) is not particularly limited. In this case, in the main chain of the acrylic resin, the structure shown in formula (4) can be continuous or discontinuous; and the structure shown in formula (5) can be continuous or discontinuous; and the structure shown in formula (6) can be continuous or discontinuous.

[0066] Here, we will further explain the meaning of R6 in formula (5) as including at least one of glycidyl group and epoxidized alkyl group among hydrogen atom, alkyl group, glycidyl group and epoxidized alkyl group. As a premise, there is one R6 in a structure shown by formula (5). We will explain the cases where the acrylic resin has only one structure shown by formula (5) and the cases where it has more than two structures.

[0067] In the former case, i.e., when the acrylic resin has a structure as shown in formula (5), R6 is a glycidyl group or an epoxidized alkyl group.

[0068] In the latter case, when the acrylic resin has two or more structures represented by formula (5), at least one of the R6 in the structure represented by formula (5) is a glycidyl group or an epoxidized alkyl group, and the remaining R6 in the structure represented by formula (5) is a hydrogen atom or an alkyl group. Since at least one R6 in the structure represented by formula (5) is a glycidyl group or an epoxidized alkyl group, it is also possible for all the R6 in the structure represented by formula (5) to be glycidyl groups or epoxidized alkyl groups.

[0069] The structure shown in formula (6) has Ph (phenyl), -COOCH2Ph, and -COO(CH2)2Ph. Since Ph, -COOCH2Ph, and -COO(CH2)2Ph have thermal stability, the strength of the cured resin composition can be improved, and the heat resistance of the laminate (metal foil laminate and wiring board) can be improved.

[0070] The styrene copolymers that can be used in this embodiment are copolymers obtained by polymerizing two or more monomers containing styrene monomers. There are no particular limitations as long as the weight average molecular weight is within the above range. Examples include: methylstyrene (ethylene / butene) methylstyrene block copolymers; methylstyrene (ethylene-ethylene / propylene) methylstyrene block copolymers; styrene-isoprene block copolymers; hydrogenated styrene-isoprene-styrene block copolymers; styrene (ethylene / butene) styrene block copolymers; styrene (ethylene-ethylene / propylene) styrene block copolymers; methylstyrene (styrene / butadiene random copolymer block) methylstyrene copolymers, styrene (styrene / butadiene random copolymer block) styrene copolymers, styrene-butadiene-styrene block copolymers, etc.; styrene-isobutylene-styrene block copolymers; styrene (butadiene / butene) styrene block copolymers; and at least a portion of their hydrogenated hydrides, etc.

[0071] As the styrene copolymers mentioned above, commercially available products can be used, or products such as Tuftec P1500, Tuftec H1221, Tuftec H1041, Tuftec H1517, Tuftec M1913, Tuftec M1981, SOE1605 manufactured by Asahi Kasei Corporation, and ASAPRENE T437 manufactured by Asahi Kasei Corporation can be used.

[0072] It should be noted that the high molecular weight substance (E-1) does not include phenolic resin (A), epoxy resin (B), maleimide compounds (C), benzoxazine compounds (D), or core-shell rubber (E-2).

[0073] The core-shell rubber (E-2) that can be used in this embodiment is an aggregate of rubber particles, each of which has a core-shell multilayer structure. The rubber particles are formed by a core and a shell. At least one of the core and shell is elastic. By including this core-shell rubber (E-2) in the resin composition, the impact resistance, thermal shock resistance, and drillability of the cured product can be improved without compromising heat resistance.

[0074] Preferably, the core-shell rubber (E-2) contains silicone in at least one of the core and the shell. This further improves thermal shock resistance. In other words, compared to the case without silicone, impact resistance is improved even at lower temperatures.

[0075] The core can help improve the toughness of the cured resin composition. The core is a particulate rubber. The rubber can be a copolymer or a homopolymer. There are no particular limitations on the polymer constituting the core, but examples include: silicone / acrylic polymers; acrylic polymers; silicone polymers; butadiene polymers; and isoprene polymers, etc.

[0076] The shell is readily compatible with the resin components in the resin composition and can contribute to improved adhesive strength. The shell is present on the surface of the core. The shell has multiple grafted chains. One end of each grafted chain is a fixed end bonded to the surface of the core, and the other end is a free end. The grafted chains can be bonded to copolymers or homopolymers. The polymer constituting the shell is not particularly limited, but examples include acrylic copolymers, polymethyl methacrylate, and polystyrene.

[0077] The 50% volume average particle size (D) of core-shell rubber (E-2) 50 The particle size is preferably 0.01 μm or more and 0.5 μm or less, more preferably 0.05 μm or more and 0.3 μm or less. This is achieved by reducing the 50% volume average particle size (D) of the core-shell rubber (E-2). 50 A particle size of 0.01 μm or larger can further improve the impact resistance of the cured material. This is achieved by reducing the 50% volume average particle size (D) of the core-shell rubber (E-2) to above 0.01 μm. 50 With a particle size below 0.5 μm, the core-shell rubber (E-2) is easily and uniformly dispersed in the resin composition, and consequently, it is also easily and uniformly dispersed in the cured product. Here, "50% volume average particle size" refers to the particle size (Dsize) at which the cumulative value of the particle size distribution reaches 50% as measured by a particle size distribution measuring device based on laser scattering and diffraction. 50 ).

[0078] (Inorganic filler material (F))

[0079] As needed, the thermosetting resin composition may contain inorganic filler (F) to a extent that does not impair the effects of the present invention. It is believed that this can improve the heat resistance, etc., of the cured resin composition.

[0080] The inorganic filler (F) is not particularly limited to any inorganic filler that can be used as an inorganic filler in the resin composition. Examples of inorganic fillers (F) include: metal oxide particles, metal hydroxide particles, molybdate particles, nitride particles, titanate particles, anhydrous magnesium carbonate particles, magnesium carbonate particles, calcium carbonate particles, quartz glass particles, talc particles, aluminum borate particles, and barium sulfate particles. Examples of metal oxide particles include: silica particles, alumina particles, titanium dioxide particles, magnesium oxide particles, and mica particles. Examples of silica particles include: spherical silica such as pulverized silica and molten spherical silica. Examples of metal hydroxide particles include: boehmite particles, magnesium hydroxide particles, and aluminum hydroxide particles. Examples of molybdate particles include: zinc molybdate particles, calcium molybdate particles, and magnesium molybdate particles. Examples of nitride particles include: aluminum nitride particles and boron nitride particles. Examples of titanate particles include barium titanate particles, strontium titanate particles, calcium titanate particles, and aluminum titanate particles.

[0081] Among these, the inorganic filler material (F) preferably comprises at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

[0082] Furthermore, the inorganic filler material (F) can be used alone, as described above, or in combination with two or more other inorganic fillers. When using two or more of the aforementioned inorganic fillers in combination, silica particles can be combined with one or more inorganic fillers other than silica particles.

[0083] The inorganic filler material (F) can be a surface-treated inorganic filler material or an untreated inorganic filler material. Furthermore, examples of surface treatment include treatment with a silane coupling agent.

[0084] (content)

[0085] The content of phenolic resin (A) relative to the total amount of resin components in the resin composition is preferably 0.1 to 60% by mass, more preferably 1 to 40% by mass. When the content of phenolic resin (A) is 0.1% by mass or more relative to the total amount of resin components in the resin composition, the decrease in adhesive strength of the cured resin composition can be suppressed, and the heat resistance can be improved. It should be noted that, in this specification, the adhesive strength of the cured resin composition refers to the adhesive strength to a metal layer (e.g., copper foil). When the content of phenolic resin (A) is 60% by mass or less relative to the total amount of resin components in the resin composition, a prepreg with a low coefficient of thermal expansion can be obtained more reliably.

[0086] In this specification, "total resin composition" refers to the total amount of resin components contained in the resin composition. For example, if the resin composition contains phenolic resin (A) and epoxy resin (B), it refers to their total; if it contains phenolic resin (A) and maleimide compound (C), it refers to their total; if it contains phenolic resin (A), epoxy resin (B), maleimide compound (C), and benzoxazine compound (D), it refers to their total (A+B+C+D). Furthermore, if the composition contains elastomer (E) in addition to phenolic resin (A), epoxy resin (B), maleimide compound (C), and benzoxazine compound (D), it refers to their total (A+B+C+D+E).

[0087] When the thermosetting resin composition contains epoxy resin (B), the content of epoxy resin (B) is preferably 10 to 80% by mass, more preferably 20 to 60% by mass, relative to the total amount of resin components in the resin composition. When the content of epoxy resin (B) is 10% by mass or more relative to the total amount of resin components in the resin composition, the decrease in the adhesive strength of the cured resin composition can be suppressed. When the content of epoxy resin (B) is 80% by mass or less relative to the total amount of resin components in the resin composition, the decrease in the glass transition temperature (Tg) can be suppressed. Furthermore, a prepreg with a low coefficient of thermal expansion can be obtained more reliably.

[0088] When the thermosetting resin composition contains maleimide compound (C), the content of maleimide compound (C) is preferably 15 to 75% by mass, more preferably 30 to 50% by mass, relative to the total amount of resin components in the resin composition. When the content of maleimide compound (C) is 15% by mass or more relative to the total amount of resin components in the resin composition, a prepreg with a low coefficient of thermal expansion can be obtained more reliably. When the content of maleimide compound (C) is 75% by mass or less relative to the total amount of resin components in the resin composition, the reduction in the adhesive strength of the cured resin composition can be suppressed.

[0089] When the thermosetting resin composition contains a benzoxazine compound (D), the content of the benzoxazine compound (D) is preferably 5 to 50% by mass, more preferably 10 to 30% by mass, relative to the total amount of resin components in the resin composition. When the content of the benzoxazine compound (D) is 5% by mass or less relative to the total amount of resin components in the resin composition, the reduction in the adhesive strength of the cured resin composition can be suppressed. When the content of the benzoxazine compound (D) is 50% by mass or less relative to the total amount of resin components in the resin composition, a prepreg with a low coefficient of thermal expansion can be obtained more reliably.

[0090] When the thermosetting resin composition contains a maleimide compound (C) and an allylbenzoxazine compound (D-1), the mass ratio of the allylbenzoxazine compound (D-1) to the maleimide compound (C) (D-1 / C) is preferably 0.3 to 1.0, more preferably 0.35 to 0.8. By making the above-mentioned mass ratio (D-1 / C) 0.3 or more, the decrease in adhesion strength to the metal layer (e.g., copper foil) can be suppressed. By making the above-mentioned mass ratio (D-1 / C) 1.0 or less, the decrease in glass transition temperature (Tg) can be suppressed.

[0091] When the thermosetting resin composition contains an elastomer (E), the content of elastomer (E) is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, relative to the total amount of resin components in the resin composition. When the content of elastomer (E) is 5% by mass or more relative to the total amount of resin components in the resin composition, a prepreg with a low coefficient of thermal expansion can be obtained more reliably. When the content of elastomer (E) is 40% by mass or less relative to the total amount of resin components in the resin composition, moldability can be improved.

[0092] When the thermosetting resin composition contains inorganic filler (F), the content of inorganic filler (F) is preferably 80 to 180 parts by weight, more preferably 100 to 150 parts by weight, relative to 100 parts by weight of the resin component in the resin composition (excluding the inorganic filler (F) in the resin composition). By having an inorganic filler (F) content of 80 to 180 parts by weight relative to 100 parts by weight of the resin component in the resin composition, a prepreg with a low coefficient of thermal expansion can be obtained more reliably. Furthermore, it helps to suppress a decrease in moldability.

[0093] The content of the thermosetting resin composition in the prepreg of this embodiment is preferably 35-80% by mass, more preferably 40-75% by mass, relative to the total amount of the prepreg. Since the content of the thermosetting resin composition in the prepreg is 35-80% by mass relative to the total amount of the prepreg, the prepreg of this embodiment can more reliably achieve the effects described above (low dielectric properties, low coefficient of thermal expansion).

[0094] (Other ingredients)

[0095] The resin composition may also contain other components (other components) besides those described above, without impairing the effects of the present invention. Examples of other components include, for instance, organic components other than those described in (A) to (E), flame retardants, reaction initiators, curing accelerators, catalysts, polymerization retardants, polymerization inhibitors, dispersants, homogenizers, coupling agents, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, and additives such as lubricants.

[0096] As described above, the resin composition according to this embodiment may also contain organic components other than components (A) to (E) mentioned above. These organic components may be, for example, compounds that react with at least one of components (A) to (E) mentioned above, or compounds that do not react. Specifically, examples of these organic components include cyanate ester compounds and reactive ester compounds.

[0097] As described above, the resin composition of this embodiment may also contain a reaction initiator. The reaction initiator is not particularly limited as long as it can promote the curing reaction of the resin composition; examples include peroxides and organic azo compounds. Examples of peroxides include α,α'-di(tert-butylperoxy)diisopropylbenzene (PBP), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, and benzoyl peroxide. Examples of organic azo compounds include azobisisobutyronitrile. Furthermore, metal salts of carboxylic acids may be used in combination as needed. This further promotes the curing reaction. A single reaction initiator may be used, or two or more may be used in combination.

[0098] As described above, the resin composition involved in this embodiment may contain a curing accelerator. The curing accelerator is not particularly limited as long as it can promote the curing reaction of the resin composition. Specifically, examples of curing accelerators include: imidazoles and their derivatives, organophosphorus compounds, amines such as secondary and tertiary amines, quaternary ammonium salts, organoboron compounds, and metal soaps. Examples of imidazoles include: 2-ethyl-4-methylimidazolium (2E4MZ), 2-methylimidazolium, 2-phenyl-4-methylimidazolium, 2-phenylimidazolium, and 1-benzyl-2-methylimidazolium. Examples of organophosphorus compounds include: triphenylphosphine, diphenylphosphine, phenylphosphine, tributylphosphine, and trimethylphosphine. Furthermore, examples of amines include: dimethylbenzylamine, triethylenediamine, triethanolamine, and 1,8-diazabicyclo(5,4,0)undecene-7 (DBU). Furthermore, examples of quaternary ammonium salts include tetrabutylammonium bromide. Furthermore, examples of the organoboron compounds include tetraphenylboron salts such as 2-ethyl-4-methylimidazole tetraphenylborate, and tetra-substituted phosphonium tetra-substituted borates such as tetraphenylphosphonium ethyltriphenylborate. Additionally, the metal soap refers to a fatty acid metal salt, which can be a linear or cyclic fatty acid metal salt. Specifically, examples of the metal soap include linear aliphatic metal salts with 6 to 10 carbon atoms and cyclic aliphatic metal salts. More specifically, examples of the metal soap include linear fatty acids such as stearic acid, lauric acid, ricinoleic acid, and octanoic acid, or cyclic fatty acids such as naphthenic acids, and aliphatic metal salts formed from metals such as lithium, magnesium, calcium, barium, copper, and zinc. Examples of the metal soap include zinc octanoate. The curing accelerator can be used alone or in combination with two or more.

[0099] [Glass cloth]

[0100] The glass cloth contained in the prepreg of this embodiment is relative to the total composition of the glass cloth, comprising: 45-55% by mass of SiO2, 20-30% by mass of Al2O3, less than 3.0% by mass of MgO, and 10-15% by mass of P2O5.

[0101] By using this glass cloth, the prepreg of this embodiment can possess excellent low dielectric properties and a low coefficient of thermal expansion.

[0102] In the glass cloth of this embodiment, if SiO2 is less than 45% by mass, it is difficult to obtain sufficient low dielectric properties; if it exceeds 55% by mass, the viscosity increases during spinning, making it difficult to fiberize. A more preferred content of SiO2 in the total amount of glass cloth is 47-53% by mass.

[0103] In the glass cloth of this embodiment, if Al2O3 is less than 20% by mass, the water resistance deteriorates; if it exceeds 30% by mass, the spinnability deteriorates and the dielectric constant increases. A more preferred content of Al2O3 in the total amount of glass cloth is 22 to 28% by mass.

[0104] In the glass cloth of this embodiment, if MgO exceeds 3% by mass, the water resistance deteriorates, and it is difficult to obtain sufficient low dielectric properties. The lower limit of the MgO content is not particularly limited, but from the viewpoint of homogenizing the glass fibers, 0.5% or more is preferred. A more preferred MgO content in the total amount of glass cloth is 0.5% to 2.8% by mass.

[0105] In the glass cloth of this embodiment, if P2O5 is less than 10% by mass, it is difficult to sufficiently suppress the hardness caused by Al2O3; if it exceeds 15% by mass, the water resistance and weather resistance may deteriorate. A more preferred content of P2O5 in the total amount of glass cloth is 10 to 14% by mass.

[0106] In addition to the components described above, the glass cloth of this embodiment may also contain approximately 0.01 to 0.05% by mass of CaO. By including CaO in the glass cloth within this range, water resistance can be improved, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0107] The glass cloth in this embodiment may also contain approximately 0.01 to 5% by mass of Na2O. By including Na2O in the glass cloth within this range, the dielectric loss factor (Df) can be further reduced, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0108] Furthermore, the glass cloth of this embodiment may also contain Li₂O and / or K₂O, and their combined content relative to the total amount of glass cloth is preferably in the range of 0.03 to 0.15% by mass, more preferably in the range of 0.04 to 0.10% by mass. It is believed that by containing Li₂O and / or K₂O in the glass cloth within this range, a low dielectric constant can be maintained, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0109] The glass cloth in this embodiment may also contain about 0.01 to 2% by mass of Fe2O3. By including Fe2O3 in the glass cloth within this range, coloration of the glass cloth can be suppressed, and the manufacturability of the glass cloth can be improved by enhancing the defoaming properties of the molten glass.

[0110] The glass cloth in this embodiment may also contain about 0.01 to 10% by mass of ZnO. By including ZnO in the glass cloth within this range, thermal expansion can be suppressed.

[0111] The glass cloth in this embodiment may also contain 0.01 to 0.10% by mass of ZrO2. By including ZrO2 in the glass cloth within this range, the alkali resistance of the glass cloth can be improved.

[0112] On the other hand, the glass cloth of this embodiment preferably contains substantially no B2O3, F2, and TiO2 (i.e., the content is less than 0.01% by mass), and more preferably contains none at all (i.e., the content is 0% by mass). By substantially containing none of these components, the elastic modulus of the glass cloth can be maintained at a higher level, and the acid resistance of the glass cloth can be improved.

[0113] The proportions of the aforementioned components in the glass cloth of this embodiment can be determined using a fluorescence X-ray analysis apparatus. Specifically, Rh can be irradiated with X-rays under a vacuum atmosphere, and analysis can be performed with an analysis diameter of 20 mmφ. Alternatively, ICP emission spectroscopy analysis can also be used for determination.

[0114] The glass cloth in this embodiment can also be a surface-treated glass cloth. As a surface treatment agent, a silane coupling agent having functional groups such as vinyl, styrene, methacryloyl, acryloyl, phenylamino is preferably used.

[0115] The glass cloth in this embodiment is preferably a glass cloth that has undergone further flattening processing. Specifically, flattening processing can be exemplified by continuously applying appropriate pressure to the glass cloth using pressure rollers to compress the yarn into a flat shape. The thickness of the glass cloth in this embodiment is not particularly limited; for example, a glass cloth of approximately 0.02 to 0.1 mm can be used without particular restriction.

[0116] In this embodiment, the glass cloth preferably accounts for about 20-65% by mass of the total amount of prepreg. By including the glass cloth in this proportion, the prepreg of this embodiment can more reliably achieve the above-mentioned effects. A more preferred proportion of glass cloth is 25-60% by mass.

[0117] [Prepreg Manufacturing Method]

[0118] Next, the method for obtaining the prepreg of this embodiment will be described. Figure 1 This is a schematic cross-sectional view illustrating an example of the prepreg 1 according to an embodiment of the present invention.

[0119] like Figure 1 As shown, the prepreg 1 according to this embodiment includes: the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2; and glass cloth 3. The prepreg 1 includes: the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2; and glass cloth 3 present in the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2.

[0120] It should be noted that, in this embodiment, a semi-cured substance is a substance that has cured a thermosetting resin composition to a state where it can still be further cured. That is, a semi-cured substance is a substance that causes the thermosetting resin composition to be in a semi-cured state (benzene curing). For example, if the thermosetting resin composition is heated, its viscosity initially gradually decreases, then begins to cure, and then gradually increases. In this case, the state from the time the viscosity begins to increase until complete curing can be listed as a semi-cured substance.

[0121] Furthermore, the prepreg obtained using the thermosetting resin composition according to this embodiment can be, as described above, a prepreg containing a semi-cured product of the thermosetting resin composition, or a prepreg containing an uncured thermosetting resin composition. That is, it can be a prepreg containing a semi-cured product of the thermosetting resin composition (the thermosetting resin composition of stage B) and glass cloth, or a prepreg containing the thermosetting resin composition before curing (the thermosetting resin composition of stage A) and glass cloth. The thermosetting resin composition or the semi-cured product of the thermosetting resin composition can be a substance obtained by drying or heating the thermosetting resin composition.

[0122] In the manufacture of prepregs, the thermosetting resin composition 2 is mostly formulated into a varnish-like form for impregnation into the substrate, i.e., glass cloth 3, used to form the prepreg. That is, the thermosetting resin composition 2 is usually a resin varnish formulated into a varnish-like form. This varnish-like thermosetting resin composition (resin varnish) can be obtained, for example, by mixing at least one of phenolic resin (A), epoxy resin (B), and maleimide compound (C) with other resin components (benzoxazine compound (D) and elastomer (E), etc.) added as needed, and then adding inorganic filler (F) as needed and mixing them, etc.

[0123] First, at least one of the components of the thermosetting resin composition that are soluble in organic solvents, namely phenolic resin (A), epoxy resin (B), and maleimide compound (C), and other resin components (benzoxazine compound (D) and elastomer (E), etc., added as needed), are added to the organic solvent and dissolved. Heating may be performed at this time if necessary. Then, components that are insoluble in organic solvents (e.g., inorganic filler (F), etc.) are added as needed, and dispersed to a specified dispersion state using a disperser or the like, thereby preparing a varnish-like thermosetting resin composition. The organic solvent used herein is not particularly limited as long as it is capable of dissolving the free radical polymerizable compound and does not hinder the curing reaction. Specifically, examples include toluene and methyl ethyl ketone (MEK).

[0124] The method for manufacturing the prepreg 1 is not particularly limited, but examples include: impregnating a thermosetting resin composition 2, which is prepared into a varnish-like state, into a glass cloth 3 and then drying it. The thermosetting resin composition 2 is impregnated into the glass cloth 3 by impregnation and coating, etc. Impregnation can be repeated multiple times as needed. In this case, the final desired composition and impregnation amount can also be adjusted by repeatedly impregnating with multiple resin compositions of different compositions and / or concentrations.

[0125] Glass cloth 3 impregnated with a thermosetting resin composition (resin varnish) 2 is heated under desired heating conditions (e.g., heating at 80°C or higher and 180°C or lower for 1 minute or more and 10 minutes or less). Heating yields a prepreg 1 in a pre-cured (stage A) or semi-cured (stage B) state. It should be noted that the heating causes the organic solvent to evaporate from the resin varnish, thus reducing or eliminating the organic solvent.

[0126] The prepreg of this embodiment possesses both low dielectric properties and a low coefficient of thermal expansion. Therefore, the wiring board having an insulating layer formed using the prepreg of this embodiment exhibits excellent low dielectric properties and experiences less warping. Thus, the prepreg of this embodiment is suitable for use in forming insulating layers disposed on metal-clad laminates and wiring boards.

[0127] <Metal Foil Coated Laminate>

[0128] Figure 2 This is a schematic cross-sectional view showing an example of the metal foil laminate 11 involved in this embodiment.

[0129] like Figure 2 As shown, the metal foil-coated laminate 11 includes: Figure 1The insulating layer 12 of the cured prepreg 1 shown; and the metal foil 13 laminated together with the insulating layer 12. That is, the metal foil laminate 11 includes: an insulating layer 12 comprising a cured thermosetting resin composition; and a metal foil 13 disposed on the insulating layer 12. The insulating layer 12 may be formed from the cured thermosetting resin composition or from the cured prepreg. The thickness of the metal foil 13 varies depending on the performance requirements of the final wiring board and is not particularly limited. The thickness of the metal foil 13 may be appropriately set according to the required purpose, for example, preferably 0.2 to 70 μm. Examples of the metal foil 13 include copper foil and aluminum foil. In the case of a thinner metal foil, a carrier-supported copper foil with a release layer and a carrier may be used to improve operability.

[0130] As for the method of manufacturing the metal-clad laminate 11, there is no particular limitation as long as the metal-clad laminate 11 can be manufactured. Specifically, a method of manufacturing the metal-clad laminate 11 using prepreg 1 can be cited. As a method, a method can be cited that involves taking a piece of prepreg 1 or stacking several pieces of prepreg 1, and then stacking a metal foil 13 such as copper foil on its upper and lower surfaces or one side surface, and heating and pressing the metal foil 13 and the prepreg 1 to form a laminate integrally, thereby manufacturing a laminate 11 with metal foil on both sides or one side surface. That is, the metal-clad laminate 11 is obtained by stacking metal foil 13 on the prepreg 1 and heating and pressing it. The heating and pressing conditions can be appropriately set according to the thickness of the metal-clad laminate 11 being manufactured or the type of composition of the prepreg 1. For example, the temperature can be set to 170 to 230°C, the pressure to 3 to 5 MPa, and the time to 60 to 150 minutes.

[0131] <Wiring board>

[0132] Figure 3 This is a schematic cross-sectional view showing an example of the wiring board 21 involved in this embodiment.

[0133] like Figure 3 As shown, the wiring board 21 according to this embodiment includes: Figure 1 The insulating layer 12 is used after curing the prepreg 1 shown; and the wiring 14 is formed by laminating the insulating layer 12 together with a portion of the metal foil 13 removed. The insulating layer 12 is formed from the cured prepreg.

[0134] The method for manufacturing the wiring board 21 is not particularly limited as long as it can be manufactured. Specifically, methods such as using the prepreg 1 to manufacture the wiring board 21 can be listed. As a method, for example, etching the metal foil 13 on the surface of the metal foil laminate 11 manufactured as described above to form wiring, thereby manufacturing a wiring board 21 with wiring as a circuit on the surface of the insulating layer 12. That is, the wiring board 21 can be obtained by removing a portion of the metal foil 13 on the surface of the metal foil laminate 11, thereby forming a circuit. In addition, as a method for forming a circuit, besides the methods described above, methods such as forming a circuit by a semi-additive process (SAP) or a modified semi-additive process (MSAP) can be listed.

[0135] Metal foil laminates and wiring boards having an insulating layer comprising a cured prepreg of the present embodiment have the same advantages as the prepreg described above, and are therefore useful for industrial applications.

[0136] This specification discloses various techniques as described above, the main techniques of which are summarized below.

[0137] The prepreg of the first technical solution comprises: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains at least one of phenolic resin (A), epoxy resin (B), and maleimide compound (C), and the glass cloth contains, relative to the total amount of the glass cloth, 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0138] In the prepreg of the second technical solution, the content of phenolic resin (A) in the thermosetting resin composition is 0.1 to 60% by mass relative to the total amount of resin components in the thermosetting resin composition.

[0139] The prepreg of the third technical solution is in the prepreg of the first or second technical solution, wherein the thermosetting resin composition further contains a benzoxazine compound (D).

[0140] The prepreg of the fourth technical solution is in the prepreg of any one of the first to third technical solutions, wherein the thermosetting resin composition contains an elastomer (E) comprising at least one of a high molecular weight substance (E-1) with a weight average molecular weight of more than 10,000 and less than 900,000 and a core-shell rubber (E-2).

[0141] The prepreg of the fifth technical solution is in the same way as the prepreg of the fourth technical solution, wherein the high molecular weight substance (E-1) comprises at least one of an acrylic resin and a styrene copolymer.

[0142] In the prepreg of the sixth technical solution, the content of elastomer (E) in the thermosetting resin composition is 5 to 40% by mass relative to the total amount of resin components in the thermosetting resin composition.

[0143] The prepreg of the seventh technical solution, in any one of the prepregs of the first to sixth technical solutions, the thermosetting resin composition further contains an inorganic filler (F), the inorganic filler (F) comprising at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

[0144] In the prepreg of the eighth technical solution, the content of the thermosetting resin composition in the prepreg is 35 to 80% by mass relative to the total amount of components in the prepreg.

[0145] The metal foil laminate of the ninth technical solution includes: an insulating layer of a cured prepreg containing any one of the technical solutions 1 to 8; and a metal layer.

[0146] The wiring board of the 10th technical solution includes: an insulating layer of cured prepreg containing any one of the technical solutions 1 to 8; and wiring.

[0147] The present invention will be further described in detail below through embodiments; however, the scope of the present invention is not limited to these embodiments.

[0148] Example

[0149] The present invention will be further described in detail below through embodiments; however, the scope of the present invention is not limited to these embodiments.

[0150] First, the components used in preparing the prepreg in this embodiment will be explained.

[0151] [Thermosetting resin composition]

[0152] (Phenolic resin (A))

[0153] Phenolic formaldehyde varnish resin (manufactured by DIC Corporation, product name "TD2090")

[0154] (Epoxy Resin (B))

[0155] • Epoxy Resin 1: Triphenolmethane-based epoxy resin (manufactured by DIC Corporation, product name "HP-7241")

[0156] • Epoxy Resin 2: A multifunctional epoxy resin with a biphenylene structure (manufactured by Nippon Kayaku Co., Ltd., product name "NC-3500")

[0157] (maleimide compound (C))

[0158] ·3,3'-Dimethyl-5,5'-Diethyl-4,4'-Diphenylmethane bismaleimide (manufactured by Daiwa Chemical Industry Co., Ltd., product name "BMI-5100")

[0159] (Benzoxazine compound (D))

[0160] • The benzoxazine compound shown in formula (3) with R3 and R4 being allyl, Y being methyl, and b and c being 1 (manufactured by Shikoku Chemical Industry Co., Ltd., product name "ALP-d")

[0161] (Elastomer (E))

[0162] • Elastomer-1 (Acrylic Elastomer): Epoxy modified acrylic resin (manufactured by Nagase ChemteX Co., Ltd., product name "PASR-001", weight average molecular weight Mw: 500,000)

[0163] • Elastomer-2: Core-shell rubber (manufactured by Mitsubishi Chemical Corporation, product name "SRK200A", core: silicone / acrylic acid copolymer, shell: acrylonitrile / styrene, D 50 (0.15μm)

[0164] (Inorganic filler material (F))

[0165] • Silica particles: spherical silica particles with phenylaminosilane surface treatment (manufactured by Admatechs Company Limited, product name "SC2500-SXJ")

[0166] (Curing accelerator)

[0167] ·2-Ethyl-4-methylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., product name "2E4MZ")

[0168] (Reaction initiator)

[0169] • Organic peroxide: PBP (1,3-bis(butylperoxyisopropyl)benzene; manufactured by Nippon Oil Co., Ltd., product name "PERBUTYL P")

[0170] [Glass cloth]

[0171] (1-3 pieces of glass cloth)

[0172] Three types of glass cloths 1 to 3 (0.1 mm thick) with the compositions shown below were prepared. It should be noted that glass cloth 1 is equivalent to conventional T-glass, and glass cloth 2 is equivalent to conventional S-glass.

[0173] • Glass cloth 1: T-glass manufactured by Nitto Boshoku Co., Ltd., type 2118 (SiO2: 66% by mass, Al2O3: 25% by mass, MgO: 7.3% by mass, and P2O5: 0% by mass).

[0174] • Glass cloth 2: S3 glass, type 2118 manufactured by Nan Ya Plastics Industrial Co., Ltd. (SiO2: 66% by mass, Al2O3: 25% by mass, MgO: 6.1% by mass, and P2O5: 0.003% by mass)

[0175] • Glass cloth 3: V-type glass manufactured by Nitto Boshoku Co., Ltd., type 2118 (SiO2: 50% by mass, Al2O3: 25% by mass, MgO: 2.3% by mass, and P2O5: 12% by mass).

[0176] [Examples 1-3 and Comparative Examples 1-5]

[0177] (Evaluation of sample preparation)

[0178] First, a resin varnish was prepared. All components except the inorganic filler were added to methyl ethyl ketone (MEK) according to the compositions (parts by mass) listed in Tables 1 and 2 and mixed to achieve a solids concentration of 40–50% by mass. The resulting mixture was stirred for 60 minutes. Then, the inorganic filler was added to the resulting mixture according to the compositions (parts by mass) listed in Tables 1 and 2, and dispersed using a bead mill. Through this process, a varnish-like resin composition (varnish) was obtained.

[0179] Next, the varnish obtained above was impregnated into the glass cloths shown in Tables 1 and 2, respectively. Specifically, glass cloth 3 was used in Examples 1-3, glass cloth 2 was used in Comparative Examples 1-4, and glass cloth 1 was used in Comparative Examples 2-3-5. Then, the prepreg was prepared by heating and drying at 130°C for 3 minutes. At this time, the content of the component constituting the resin through the curing reaction was adjusted to be approximately 45% by mass relative to the content of the prepreg (resin content). That is, the content of glass cloth was adjusted to be 55% by mass relative to the total amount of prepreg. In addition, the curing thickness was adjusted to reach 103 μm.

[0180] Next, evaluation samples (metal foil laminates) were obtained using the obtained prepreg. First, 10 sheets of the obtained prepreg were overlapped, and copper foil (3EC-VLP manufactured by Mitsui Metals & Mining Co., Ltd.) with a thickness of 12 μm was placed on both sides. Using it as a pressing body, it was heated to a temperature of 220°C at a heating rate of 3°C / min, and then heated and pressurized at 220°C for 120 minutes and a pressure of 4 MPa, thereby obtaining an evaluation substrate (metal foil laminate) with a resin layer (insulating layer) of approximately 1030 μm thick on both sides with copper foil bonded to it.

[0181] Evaluation test 1 was conducted using the evaluation substrate prepared as described above and the method shown below.

[0182] [Evaluation Test]

[0183] In the evaluation tests of dielectric properties (relative permittivity Dk) and coefficient of thermal expansion, the bare board (cured prepreg, approximately 1030 μm thick) after removing the copper foil from the copper-clad laminate obtained by etching 10 overlapping prepreg sheets was used as the evaluation sample.

[0184] (Dielectric properties (relative permittivity: Dk))

[0185] The relative permittivity (Dk) of the evaluation sample at 10 GHz was determined using the resonant cavity perturbation method. Specifically, the relative permittivity of the evaluation substrate at 10 GHz was determined using a network analyzer (Keysight Technologies N5230A).

[0186] (Coefficient of thermal expansion: CTE (50~260℃))

[0187] The evaluation sample (size: 10.0 mm × 3.5 mm) was used as a test piece, and the coefficient of thermal expansion (CTE) of the evaluation substrate in the planar direction (Y direction) at a temperature below the glass transition temperature of the cured resin composition was determined by TMA (Thermo-mechanical analysis). Specifically, the measurement was performed in compression mode using a TMA apparatus (TMA / SS7100 manufactured by Seiko Electronics Nanotechnology Co., Ltd.). To eliminate the influence of thermal strain on the test piece, a 10 g load was applied to the test piece along the Y direction, and the temperature was increased from 30 °C to 320 °C at a heating rate of 10 °C / min, and then cooled to room temperature. Then, a 10 g load was applied to the test piece along the Y direction, and the temperature was increased from 30 °C to 320 °C at a heating rate of 10 °C / min. During this heating, a temperature shift diagram was obtained. Then, based on the temperature shift diagram obtained at this time, the average coefficient of thermal expansion (CTE) from 50 to 260 °C was calculated. The lower the average coefficient of thermal expansion, the better the result.

[0188] The results of the above evaluations are shown in Tables 1 and 2.

[0189]

[0190]

[0191] [Inspection]

[0192] As shown in Tables 1 and 2, it was confirmed that the prepregs of Examples 1 to 3, which used the resin composition and glass cloth of this embodiment, exhibited lower dielectric properties (relative permittivity) and coefficients of thermal expansion. Example 2, as an elastomer (E), contained a high molecular weight material with a weight-average molecular weight of 10,000 or more and 900,000 or less, and a core-shell rubber. In this case, it was also confirmed that the dielectric properties (relative permittivity) and coefficients of thermal expansion were lower.

[0193] On the other hand, the prepregs of Comparative Examples 1-3, which did not use the glass cloth of this embodiment, exhibited at least one of lower dielectric properties (lower relative permittivity) and lower coefficient of thermal expansion that were worse than those of Examples 1-2. Furthermore, the prepregs of Comparative Examples 4-5, which did not use the glass cloth of this embodiment, also exhibited at least one of lower dielectric properties (lower relative permittivity) and lower coefficient of thermal expansion that were worse than those of Example 3.

[0194] This application is based on Japanese Patent Application No. 2024-56464, filed on March 29, 2024, the contents of which are incorporated herein by reference.

[0195] To illustrate the invention, it has been adequately and sufficiently described above with reference to the accompanying drawings and embodiments. However, it should be understood that modifications and / or improvements to the above embodiments can be readily made by those skilled in the art. Therefore, any modifications or improvements made by those skilled in the art that do not depart from the scope of the claims are to be construed as being included within the scope of the claims.

[0196] Industrial availability

[0197] According to the present invention, it is possible to provide a prepreg with excellent low dielectric properties and a low coefficient of thermal expansion, and a metal foil laminate and wiring board using the prepreg.

Claims

1. A prepreg, characterized in that... include: Thermosetting resin composition or a semi-cured product of said thermosetting resin composition; And glass cloth, among which, The thermosetting resin composition contains at least one of phenolic resin (A), epoxy resin (B), and maleimide compound (C). Relative to the total composition of the glass cloth, the glass cloth contains: 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

2. The prepreg according to claim 1, characterized in that, The content of phenolic resin (A) in the thermosetting resin composition is 0.1 to 60% by mass relative to the total amount of resin components in the thermosetting resin composition.

3. The prepreg according to claim 1, characterized in that, The thermosetting resin composition also contains a benzoxazine compound (D).

4. The prepreg according to claim 1, characterized in that, The thermosetting resin composition contains an elastomer (E) comprising at least one of a high molecular weight substance (E-1) with a weight average molecular weight of 10,000 or more and 900,000 or less, and a core-shell rubber (E-2).

5. The prepreg according to claim 4, characterized in that, The high molecular weight substance (E-1) includes at least one of acrylic resin and styrene copolymer.

6. The prepreg according to claim 4, characterized in that, The content of elastomer (E) in the thermosetting resin composition is 5 to 40% by mass relative to the total amount of resin components in the thermosetting resin composition.

7. The prepreg according to claim 1, characterized in that, The thermosetting resin composition also contains inorganic filler (F). The inorganic filler material (F) comprises at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

8. The prepreg according to claim 1, characterized in that, The content of the thermosetting resin composition in the prepreg is 35 to 80% by mass relative to the total amount of components in the prepreg.

9. A metal foil-coated laminate, characterized in that... include: An insulating layer comprising the prepreg of any one of claims 1 to 8; as well as Metal layer.

10. A wiring board, characterized in that... include: An insulating layer comprising the prepreg of any one of claims 1 to 8; as well as wiring.

Citation Information

Patent Citations

  • Schedule management system and event management server and scheduler terminal and program and method for schedule management

    JP2024056464A

  • Glass fiber–reinforced resin molded article

    WO2017171101A1

  • Laminate, printed wiring board, semiconductor package, and method for manufacturing laminate

    WO2020130007A1

  • Glass fiber-reinforced resin molded product

    WO2022075273A1